1995
DOI: 10.1007/bf02431253
|View full text |Cite
|
Sign up to set email alerts
|

Use of prolamine polymorphism in studying genetic resources of forage grasses

Abstract: Electrophoresis of single seed prolamines was used for the analysis of Lolium perenne L., Festuca pratensis Huds., and Dac~lis glomerata L. populations. Identification and registration of populations was carried out according to the frequencies of occurrence of genotypes with corresponding types of prolamine banding patterns. The publication sums up the problems of applied use of molecular markers for identification and registration of world genetic resources of forage grasses, analysis of the dynamics of popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
1
3
0
3
Order By: Relevance
“…The present research confirmed conclusions of Konarev et al (1995Konarev et al ( , 1996, Steiner et al (1997), Kresovich et al (1997), Hodgkin (1997) or Bo¨rner et al (2000) about the necessity to control the genotypic structure or genetic integrity of accessions reproduced in genebanks. In fact, genebank pioneers as Vavilov, Mansfeld or Lehmann outlined the requirement for the description of accessions in genebank collections and suggested the comparison with reference material for monitoring the status of genebank accessions after regeneration already decades earlier (Mansfeld 1951;Lehmann and Mansfeld 1957).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…The present research confirmed conclusions of Konarev et al (1995Konarev et al ( , 1996, Steiner et al (1997), Kresovich et al (1997), Hodgkin (1997) or Bo¨rner et al (2000) about the necessity to control the genotypic structure or genetic integrity of accessions reproduced in genebanks. In fact, genebank pioneers as Vavilov, Mansfeld or Lehmann outlined the requirement for the description of accessions in genebank collections and suggested the comparison with reference material for monitoring the status of genebank accessions after regeneration already decades earlier (Mansfeld 1951;Lehmann and Mansfeld 1957).…”
Section: Discussionsupporting
confidence: 95%
“…A large number of such researches was made by using isozymes and storage proteins (Konarev et al 1995(Konarev et al , 1996Allard 1997). More recently, DNA-marker techniques in general but microsatellite markers in particular were applied for these purposes (Weising et al 1995;Kresovich et al 1997;Bo¨rner et al 2000;Chebotar et al 2003).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Более надежную информацию о возможной дублетной природе образцов дает использование морфологических, агрономических или селекционно ценных признаков, а в последнее время -молекулярных маркеров (Ruiz, Aguiriano, 2004;Diederichsen, 2009;Yndgaard et al, in print). Успешное многолетнее использование белковых маркеров, особенно запасных белков семян, в идентификации сортов, биотипов и линий различных культур, включая оценку степени генетического родства, позволяет применять данный подход и для мониторинга «дублетности» ( Konarev V., 1983;Hintum, Visser, 1995;Konarev et al, 1995;Molecular…, 1996;Portyanko et al, 1998;Identification…, 2000;Romanova et al, 2001;Konarev et al, 2002;Pomorcev, Lyalina, 2003;Zelenskaya et al, 2004;Ruiz, Aguiriano, 2004;Konarev et al, 2005). ДНК-маркеры (RAPD-, RFLP-, ALFP-, SSR-анализ) также активно адаптируются для решения рассматриваемой проблемы (Virk et al, 1995;Willner et al, 1998;Verma et al, 1999;Bradley et al, 2002;Lund et al, 2003;Dobrovolskaya et al, 2005;Fu, 2006).…”
Section: Introductionunclassified